Outlook of the process of storage of oncology drugs from the logistic operator in Colombia - Sánchez-Calvera, Pedro Vicente (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2014)
This article mainly on the problem of  storage of oncology drugs, which is an important element in the supply chain, applied in the context of warehouse management of oncology drugs, in the logistics operator and providers of health services institutions (IPS for its acronym in Spanish) of Bogotá DC and in the contex of a macro project "Methodological proposal for the definition of policies , rules of negotation and coordination in supply management of oncology drugs in Colombia," funded by Colciencias and the Universidad Nacional of Colombia. This article presents the current situation of oncology drugs, marking a characterization, diagnosis and identification and startegies evaluated under different scenarios. Finally, it is presented a proposal of improvement applied tranversely to storage processes including labels such as just in Time and the application of information and communication technologies (ICT).